The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/rs70100788
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Aboveground Biomass in Dense Tropical Submontane Rainforest Using Airborne Laser Scanner Data

Abstract: Successful implementation of projects under the REDD+ mechanism, securing payment for storing forest carbon as an ecosystem service, requires quantification of biomass. Airborne laser scanning (ALS) is a relevant technology to enhance estimates of biomass in tropical forests. We present the analysis and results of modeling aboveground biomass (AGB) in a Tanzanian rainforest utilizing data from a small-footprint ALS system and 153 field plots with an area of 0.06-0.12 ha located on a systematic grid. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 57 publications
2
50
2
Order By: Relevance
“…The final model was based on percentile height (H.p25) and canopy cover (CC.all.first). The variables are in line with the previous studies in Africa, which have used, for example, mean canopy height, height percentiles and canopy density for modelling [6,[10][11][12]. Both modelling accuracy and explanatory variables are similar to the model used for the hills in the study by [15], who developed separate models for hills and lowlands using different ALS data.…”
Section: Als-based Aboveground Biomass Mapsupporting
confidence: 63%
“…The final model was based on percentile height (H.p25) and canopy cover (CC.all.first). The variables are in line with the previous studies in Africa, which have used, for example, mean canopy height, height percentiles and canopy density for modelling [6,[10][11][12]. Both modelling accuracy and explanatory variables are similar to the model used for the hills in the study by [15], who developed separate models for hills and lowlands using different ALS data.…”
Section: Als-based Aboveground Biomass Mapsupporting
confidence: 63%
“…Taking the design-based approach to variance estimation d'Oliveira et al [49], reported a relative efficiency of 3.4 in a study utilising 50 plots of ~0.25 ha in the Brazilian Amazon. We can similarly compute the relative efficiency from the variance estimates reported by Hansen et al [10]. For a plot size of ~0.1 ha the relative efficiency was 2.1.…”
Section: Resultsmentioning
confidence: 97%
“…Modelling of biomass using image matching requires a high quality digital terrain model (DTM) as reference surface, usually derived from airborne laser scanning (ALS). ALS is itself a remote sensing technology that provides three-dimensional data of the forest vegetation and has been used successfully for biomass estimation, even in tropical areas [9,10]. Another technology that provides three-dimensional data is synthetic aperture radio detection and ranging (SAR).…”
Section: Introductionmentioning
confidence: 99%
“…2017, 9, 18 3 of 16 pine woodlands using field data collected at 0.25, 0.5, and 1 ha, and a weak dependence using data at 0.1 ha. However, due to the high amount of resources needed to set up and monitor forest plots, it is difficult to establish large sampling areas and obtain field datasets based on large plots [28]; thus, small plots are much more used than large ones in biomass research and mapping activities.…”
Section: Introductionmentioning
confidence: 99%